Model Pembelajaran Model Jigsaw: Model Pembelajaran Berbasis Kolaborasi - Az Zahwa Maghfirah; Nur Fadila; Ghina Fadiyah; Raoda Raoda; Putri Aisyah; Rifdah Khalishah (PT. Citra Media Publishing, 2025)
Jigsaw cooperative learning is an effective method to improve students’ conceptual understanding, motivation to learn, and active participation. Through small group learning, students learn a specific section of the material and then teach the material to their classmates. This process strengthens students’ understanding, social skills, and critical thinking skills. Research shows that the Jigsaw model can improve academic learning outcomes, especially in complex subjects such as mathematics and science, and develop students’ metacognitive abilities. In addition, this model encourages inclusive collaboration and improves social-emotional skills, creating an interactive and enjoyable learning environment. Although effective, the implementation of this model in Indonesia faces challenges, such as difficulties in time management and the need for intensive teacher guidance to ensure that each student understands their role in the group. This study uses a qualitative descriptive approach with a literature study, which aims to analyze the advantages and obstacles to implementing the Jigsaw model in the context of education in Indonesia.